Level of Financial Literacy of Women Informal Sector Workers on Welfare and Professionalisme - Nazihah, Naura; Rusdjijati, Retno; Murniningsih, Rochiyati (Universitas Muhammadiyah Magelang, 2022)
Women dominate informal sector workers, as their working hours are irregular and do not require expertise and skills based on specialized formal education. The problem faced by workers is the level of welfare and professionalism that is not optimal. There are still many who live in poverty and do not work wholeheartedly. Likely influenced by low financial literacy. Therefore, this study aims to examine the influence of welfare and professionalism on financial literacy. The Stratified Random Sampling method was used to determine the sample and 487 respondents were obtained. The research data obtained were then processed using multiple linear regression SPSS. The hypothesis testing method uses a significance level of 5%. The results showed that well-being has a simultaneous effect on financial literacy. Professionalism simultaneously affects financial literacy